2013
DOI: 10.1194/jlr.r034025
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the determination of HDL structure by apolipoproteins

Abstract: This article is available online at http://www.jlr.orgThe purpose of this review is to summarize current understanding of how apolipoproteins (apoA-I in particular) determine the structures of HDL particles. The focus is on recent advances in the fi eld, so the coverage of the literature on HDL structure is not comprehensive. Knowledge of HDL structure at the molecular level is critical for understanding how this lipoprotein achieves the multiple functions elaborated in other reviews in this thematic series.In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(113 citation statements)
references
References 122 publications
4
109
0
Order By: Relevance
“…The release of PL and FC from the PM involves PL bilayer solubilization due to the detergent-like properties of the apoA-I molecule (112,113). The solubilization process involves insertion of amphipathic α-helices between the PM PL molecules which destabilizes and fragments the bilayer (114).…”
Section: Abca1-mediated Pl-apoa-i Interactionmentioning
confidence: 99%
“…The release of PL and FC from the PM involves PL bilayer solubilization due to the detergent-like properties of the apoA-I molecule (112,113). The solubilization process involves insertion of amphipathic α-helices between the PM PL molecules which destabilizes and fragments the bilayer (114).…”
Section: Abca1-mediated Pl-apoa-i Interactionmentioning
confidence: 99%
“…Fourth, extensive biophysical studies, including protein cross-linking followed by mass spectrometry and distance measurements using FRET or EPR, indicate that the 4-helix bundles in apoA-I, apoA-IV and apoE open up on the lipid to form two pairs of helices that wrap around the lipoprotein perimeter in an antiparallel “double-belt” conformation ([4650] and references therein). Such a helix bundle opening exposes the apolar faces of the amphipathic apolipoprotein α-helices to the lipid surface (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers indicated that the composition of plasma phospholipids in blood directly reflect short-term (several days) physiological changes (e.g. dietary fat intake) [13], while the erythrocytes have a half-life in circulation of approximately 120 days in blood and their membrane phospholipids are remodeled throughout the cell's life span by the ingestion of phospholipids from blood circulation [14,15]. Thus, the phospholipid compositions of erythrocyte membrane are thought to indirectly reflect physiological change over a period of months [16].…”
Section: Introductionmentioning
confidence: 99%